Filth-Breeding Flies - P.G. Koehler; J.L. Castner (EDIS)
This document provides an overview of filth-breeding flies in Florida, detailing their physical characteristics, behaviors, and habitats. It covers species such as the house fly, greenbottle fly, bluebottle fly, secondary screwworm fly, vinegar fly, flesh fly, moth fly, eye gnat, humpbacked fly, and soldier fly. Each section highlights unique features, such as breeding preferences and identifying marks. The document aims to educate readers on recognizing and managing these common pests. Date first printed: November 1992.